Magnetic endoscopic imaging as an adjuvant to elective colonoscopy: a systematic review and meta-analysis of randomized controlled trials - Mark-Christensen, Anders; Brandsborg, Søren; Iversen, Lene Hjerrild (Endoscopy, 2015)
Background and study aims: The use of magnetic endoscopic imaging (MEI) to visualize scope configuration in three dimensions is thought to increase procedural efficiency and diminish discomfort associated with colonoscopy. The aim of this systematic review and meta-analysis was to evaluate the performance of MEI in colonoscopy. Methods: The electronic databases Medline, EMBASE, and the Cochrane Library of Randomized Trials were searched. Methodological quality was assessed using the Jadad score. Odds ratios (OR) or risk differences for dichotomous variables and mean differences for continuous outcomes were calculated with 95 % confidence intervals (CIs).Results: A total of 13 randomized studies met eligibility criteria and were included in qualitative and quantitative synthesis. MEI was associated with a significantly lower risk of failed cecal intubation (risk difference 4 %, 95 %CI 0 % – 7 %; P = 0.03), lower cecal intubation time (mean difference 0.58 minutes, 95 %CI 0.28 – 0.88; P < 0.001), and lower pain scores as estimated by visual analog scales (mean difference 0.45 cm, 95 %CI 0.03 – 0.86; P = 0.03) compared with conventional colonoscopy. On subgroup stratification of outcome according to endoscopist experience, failure rates were unaffected, but experienced colonoscopists reduced intubation times with MEI (mean difference 0.78 minutes, 95 %CI 0.12 – 1.43; P = 0.02). Sensitivity analyses of high-quality studies (Jadad score ≥ 3) showed no significant difference in failure rate (risk difference 4 %, 95 %CI 0 % – 8 %; P = 0.07) or intubation time (mean difference 0.56 minutes, 95 %CI – 0.15 to 1.28; P = 0.12).Conclusion: Adjuvant MEI is associated with a lower failure risk and shorter time to cecal intubation during elective colonoscopy compared with conventional colonoscopy.